Implementation of the OSTRC Handball Injury Prevention Exercises in Professional Handball - Wesam Saleh A. Al Attar; Nawaf Al Masoudi; Ali Al Zubeadi; Ahmed Qasem (OVS LLC, 2021)
Purpose. The Oslo Sports Trauma Research Center (OSTRC) handball injury prevention exercise is an evidence-based injury prevention exercise designed to prevent handball injury. This study aimed to assess the implementation of the OSTRC handball injury prevention exercises among professional handball players in the Gulf Cooperation Council (GCC) countries. Materials and methods. A web-based survey to acquire information regarding the implementation of OSTRC handball injury prevention exercises was distributed to 267 professional handball players in six GCC countries.  Results. A total of 250 handball players from the GCC countries responded to the survey (response rate 93.6%). The mean (±SD (Standard Deviation)) of the total implementation score was 13 (±2.558), with no statistically significant difference between the GCC countries, with a P-value of 0.123. The highest mean score was shown from Bahrain at 13.60 (±2.614), while the lowest was from Qatar at 12.10 (±2.427). Conclusions. A low implementation level of the OSTRC handball prevention exercises among the handball players in the GCC countries was reported in the current study.